Fuzzy Control Model and Simulation for Nonlinear Supply Chain System with Lead Times. (14th September 2017) - Zhang, Songtao; Hou, Yanting; Zhang, Siqi; Zhang, Min
Abstract : A new fuzzy robust control strategy for the nonlinear supply chain system in the presence of lead times is proposed. Based on Takagi-Sugeno fuzzy control system, the fuzzy control model of the nonlinear supply chain system with lead times is constructed. Additionally, we design a fuzzy robust H ∞ control strategy taking the definition of maximal overlapped-rules group into consideration to restrain the impacts such as those caused by lead times, switching actions among submodels, and customers' stochastic demands. This control strategy can not only guarantee that the nonlinear supply chain system is robustly asymptotically stable but also realize soft switching among subsystems of the nonlinear supply chain to make the less fluctuation of the system variables by introducing the membership function of fuzzy system. The comparisons between the proposed fuzzy robust H ∞ control strategy and the robust H ∞ control strategy are finally illustrated through numerical simulations on a two-stage nonlinear supply chain with lead times.